Coating and Pelletization of Probiotic Lactobacillus Strains to Enhance Viability During Processing and Storage - Haris, Azim (2011)
The use of probiotics is one of several approaches that have potential to be an alternative to antibiotics as growth promoters for improving livestock production. The ability of probiotic microorganisms to remain viable and stable during processing, storage and digestion is very crucial for their positive contribution to the host. However, even with sophisticated formulations under excellent storage conditions, the loss rate is about one log unit of cell reduction per year. In the present study, attempts were made to enhance the viability of three probiotic Lactobacillus strains, (L. reuteri C 10, L. gallinarium I 26 and L. brevis I 25), by coating the cells with stearic acid using a fluidized bed granulator, and by pelletization using the extrusion technique. Preliminary studies were carried out to evaluate the tolerance of L. reuteri C 10 to high temperatures (58 to 70 ºC) and acidic conditions (pH 4 to 6) because the melting point of stearic acid is 57.23 ºC and pH is 5.5, and input temperatures of the fluidized bed granulator could be as high as 70 ºC. Results of the preliminary study demonstrated that freeze-dried L. reuteri C 10 cells incorporated with cryoprotectants (trehalose and sucrose) exhibited higher survivability compared to freeze-dried L. reuteri C 10 cells without cryoprotectants when exposed for 30 min at 64, 66 and 68 ºC. Freeze-dried cells with cryoprotectants were also able to survive for 15 min at 70 ºC, but not freeze-dried cells without cryoprotectants. In acidic conditions (pH 4, 5 and 6), freeze-dried L. reuteri C 10 with cryoprotectants also exhibited higher survival rates than those without cyroprotectants. Thus, cells incorporated with cryoprotectants were used for the coating process. The use of a fluidized bed granulator to coat freeze-dried L. reuteri C 10 cells resulted in the formation of a big lump consisting of stearic acid on the upper portion, and excessive amount of freeze-dried Lactobacillus cells on the lower portion, instead of fine, uniformly-coated granules. The coating process using a fluidized bed granulator was not successful in this study due to rapid solidification of stearic acid inside the tube and spray nozzle because the melting point of stearic acid could not be maintained. Since fluidized bed coating of L. reuteri C 10 was not successful, the coating process was not carried out on L. gallinarium I 26 and L. brevis I 25, An alternative technique, which was a pelletization technique, was then carried out to pelletize L. reuteri C 10, L. gallinarium I 26 and L. brevis I 25 using the extrusion-spheronization technique and the extrusion-grinding technique. The extrusion-grinding technique was designed and developed in this study. It was a simple technique, very easy to handle and did not require expensive sophisticated equipment as in the extrusion-spheronization technique. The results revealed that the extrusion-grinding technique produced less (P < 0.001) cell loss during processing than the extrusion-spheronization technique. A loss of 0.5 to 1.3 log units of viable cells from the granulation to the spheronization or grinding process was observed in both the extrusion-spheronization and extrusion-grinding techniques used. However, the extrusion-grinding technique showed significantly (P < 0.001) higher cell viability during the freeze-drying process compared to the extrusion-spheronization technique (approximately 50 % and 77 % of cell loss, respectively). Three formulations (A, B and C, with varied compositions of microcrystalline cellulose, lactose, inulin and skim milk) were used to pelletize Lactobacillus strains in the extrusion-spheronization and extrusion-grinding processes. The results showed that, generally, formulation A was the best (P < 0.001) formulation to pelletize Lactobacillus cells using both extrusion-spheronization and extrusion-grinding techniques. After 6 months of storage at 30 ºC, higher cell viabilities were exhibited by all three Lactobacillus strains in pellets produced by the extrusion-grinding technique than by the extrusion-spheronization technique. However, at 4 ºC, only L. reuteri C 10 but not L. gallinarium I 26 and L. brevis I 25, exhibited higher (P < 0.001) cell viability in pellets produced from the extrusion-grinding technique than from the extrusion-spheronization technique throughout 6 months of storage. Formulations A and B were better (P < 0.001) than formulation C in maintaining higher cell viability during 6 months of storage at 4 and 30 ºC, regardless of the techniques used. The results for the pellet densities showed that pellets from the extrusion-grinding technique had higher (P < 0.001) density compared to those from the extrusion-spheronization technique. Denser pellets (from extrusion-grinding technique) might provide better protection against adverse environmental conditions during storage, especially at 30 ºC (room temperature). In conclusion, the use of fluidized bed granulator to coat L. reuteri C 10 with stearic acid was not successful. The simple extrusion-grinding technique designed and developed in this study produced better survival rates of Lactobacillus cells during processing and storage than the extrusion-spheronization technique.